Rede de atenção em saúde mental no município de Fortaleza : uma análise multidimensional na perspectiva de profissionais de diferentes dispositivos - Amaral, Carlos Eduardo Menezes (2013)
This work aimed to comprehend the mental health care network in the city of Fortaleza, from the perspective of workers from different services, using aqualitative hermeneutic approach. We developed conceptual-analytical model for networks, with five dimensions: 1) minimum units; 2) connectivity; 3) integration; 4) normativities; 5) subjectivity. The research included three health services: a primary care center (CSF), a psychosocial care center (CAPS) and a psychiatric hospital (HSMM), in which we performed free observation and 21 semi-structured interviews with professionals. As results, we found different concepts of care in each service, as well as diverse internal activities flows, and entrance, discharge and referral criteria. The connections between services included six varieties: referrals, counter-reference, phone contact, manager meeting, active search and matrix support. We also mapped the interaction with other health services, and services outside the health sector, cases in which we discovered “use of space” and “partnership” as new types of connections. Also, the workers support the complementarity between the services researched, although CAPS argues for the transient nature of such relation, while HSMM believes in its permanence. The complementarity between prevention, health promotion and health recovery was also supported, although only secondary prevention and health recovery actions were identified by the workers. We also found incongruence between CAPS’s “intervention object”, defined by a broad specter of health and social needs of people with mental disorders/psychic suffering, and HSMM’s definition, limited to crisis and mental disorders itself. Furthermore, we stress as part of the subjectivity dimension the types of patient rapport developed in each service, as well as the political action toward the Psychiatric Reform from CAPS´s professionals. We conclude that our conceptual-analytical model allowed us to indicate several subtle aspects of the mental health care network of the city of Fortaleza, widening the comprehension of such network.